Image enhancement using white balance technique in Ziehl-Neelsen sputum slide images - Rafikha Aliana, A. Raof; R. Badlishah, Ahmad, Prof. Madya Dr.; Mohd Yusoff, Mashor, Prof. Dr.; Siti Suraiya, Mohd Noor, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.